Peran Pendidikan Pramuka Dalam Menumbuhkan Pendidikan Karakter Anak - I Wayan Bayu Dharmayana; Ida Bagus Alit Arta Wiguna (Padma Sari: Jurnal Ilmu Pendidikan, 2021)
Scouting activities are an educational process in the form of activities for children carried out outside family education that use the basic principles of scouting. The role of scouts in the formation of the character of students is a unique problem to be studied. In this research using qualitative research methods and which will be discussed are Scout raisers. Raising Scouts are students in the scouting movement aged between 11-15 years. activities that are challenging and interesting and contain education that is in accordance with the spiritual and physical development of students in the process of scouting education activities carried out by scout raising at SD Negeri 10 Kesiman there are twelve activities: Formation of New Groups, Red and White Codes, Password Wars, Celebrating the Anniversary of World Scouts , Panorama Sketch, Ribbon Map, Compass, Emergency First Aid Skills, Pioneering Skills, Wandering Activities, Wide Game and Camping. Activities for Raising Scouts must be in accordance with their spiritual and physical conditions and be able to improve their five areas of personal development that are packaged in an interesting, challenging and fun and varied way: Spiritual Development Area, Emotional Development Area, Social Development Area, Intellectual Development Area and Physical Development Area.